Utilisation of sexual health services by female sex workers in Nepal - van Teijlingen Edwin R; Smith W; Ghimire Laxmi (BMC, 2011)
Abstract Background The Nepal Demographic Health Survey (NDHS) in 2006 showed that more than half (56%) of the women with sexually transmitted infections (STIs), including HIV, in Nepal sought sexual health services. There is no such data for female sex workers (FSWs) and the limited studies on this group suggest they do not even use routine health services. This study explores FSWs use of sexual health services and the factors associated with their use and non-use of services. Methods This study aimed to explore the factors associated with utilisation of sexual health services by FSWs in the Kathmandu Valley of Nepal, and it used a mixed-method approach consisting of an interviewer administered questionnaire-based survey and in-depth interviews. Results The questionnaire survey, completed with 425 FSWs, showed that 90% FSWs self-reported sickness, and (30.8%) reported symptoms of STIs. A quarter (25%) of those reporting STIs had never visited any health facilities especially for sexual health services preferring to use non-governmental clinics (72%), private clinics (50%), hospital (27%) and health centres (13%). Multiple regression analysis showed that separated, married and street- based FSWs were more likely to seek health services from the clinics or hospitals. In- depth interviews with 15 FSWs revealed that FSWs perceived that personal, structural and socio-cultural barriers, such as inappropriate clinic opening hours, discrimination, the judgemental attitude of the service providers, lack of confidentiality, fear of public exposure, and higher fees for the services as barriers to their access and utilisation of sexual health services. Conclusion FSWs have limited access to information and to health services, and operate under personal, structural and socio-cultural constraints. The 'education' to change individual behaviour, health worker and community perceptions, as well as the training of the health workers, is necessary.